2012
DOI: 10.1186/1758-5996-4-32
|View full text |Cite
|
Sign up to set email alerts
|

Diet high in fat and sucrose induces rapid onset of obesity-related metabolic syndrome partly through rapid response of genes involved in lipogenesis, insulin signalling and inflammation in mice

Abstract: BackgroundFrequent consumption of a diet high in fat and sucrose contributes to lifestyle-related diseases. However, limited information is available regarding the short-term effects of such a diet on the onset of obesity-associated metabolic abnormalities.MethodsMale C57BL/6 J mice were divided into two groups and fed a standard chow diet (control group) or a high fat–high sucrose diet containing 21% fat and 34% sucrose (HF–HS diet group) for 2 or 4 weeks.ResultsThe HF–HS diet significantly induced body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
102
3
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(115 citation statements)
references
References 50 publications
6
102
3
4
Order By: Relevance
“…The downregulation of PK in obesity group and its upregulation after pomegranate juice treatment corresponds to insulin level in both conditions, as insulin was reported to upregulate PK in rat hepatocytes. 57) Parallel to molecular findings and in agreement with previous studies, 39,58,59) histological examination revealed fatty degeneration of hepatocytes (steatosis) in hepatic sections stained by oil red O from rats in groups received HFD, but not in the control group. Hepatic sections from rats in groups received HFD concurrently with pomegranate juices revealed remarkable reduction in the size and number of lipid droplets.…”
Section: Discussionsupporting
confidence: 88%
“…The downregulation of PK in obesity group and its upregulation after pomegranate juice treatment corresponds to insulin level in both conditions, as insulin was reported to upregulate PK in rat hepatocytes. 57) Parallel to molecular findings and in agreement with previous studies, 39,58,59) histological examination revealed fatty degeneration of hepatocytes (steatosis) in hepatic sections stained by oil red O from rats in groups received HFD, but not in the control group. Hepatic sections from rats in groups received HFD concurrently with pomegranate juices revealed remarkable reduction in the size and number of lipid droplets.…”
Section: Discussionsupporting
confidence: 88%
“…The HFDR ameliorated metabolic dysfunction and mitigated hyperactivation of growth factor-related signaling, such as mTOR and insulin. Our data indicate that a simple reduction of the absolute intake of an otherwise adverse diet 23 may improve metabolic health and impede cellular aging, e.g. through induction of chaperone-mediated autophagy.…”
Section: Discussionmentioning
confidence: 84%
“…The experimental diet was a purified semi-synthetic, energy-dense, high-fat, and high-sugar diet purchased from Ssniff (TD 88137 modified; Soest, Germany) that is known to rapidly induce body weight gain and adipose tissue hypertrophy in C57BL/6 mice. 23 The diet contained 17.1 grams/kg crude protein, 21.2 grams/kg crude fat, 14.5 grams/kg starch, and 32.8 grams/kg sucrose. The metabolizable energy of the diet (19.1 MJ/kg) was composed of 43% carbohydrates, 15% protein, and 42% fat with a protein-to-carbohydrate ratio of 0.35.…”
Section: Mice and Dietmentioning
confidence: 99%
“…Recent studies suggest that chronic low-grade inflammation is a characteristic of obesity (31,32). Moreover, macrophage activation in the adipose tissue is a crucial step that drives the development of obesity and related diseases (32).…”
Section: Discussionmentioning
confidence: 99%